KARAKTERISTIK SIFAT FISIK TANAH BERDASARKAN UJI KADAR AIR, BERAT JENIS, BATAS ATTEERBERG, DAN ANALISIS SARINGAN (STUDI KASUS JL. SETIA BUDI, MEDAN, SUMATERA UTARA) - Indi Rezki Uli Simanjuntak; Agnes Br. Manurung; Juni Indriani; Indra Jhon Fischer; Frans Tomy Syahputra Butarbutar (Nusantara Hasana Journal, 2026)
Soil as a construction supporting material requires accurate physical properties characterization to ensure structural stability and safety. This study aims to characterize the physical properties of soil in the area of the Civil Engineering Laboratory, Politeknik Negeri Medan through testing of water content, specific gravity, Atterberg limits, and gradation analysis. Disturbed soil samples were tested using SNI and ASTM standard procedures. The results showed an average water content of 18.45%, an average specific gravity of 2.6515, a liquid limit (LL) of 25%, and the soil exhibited non-plastic (NP) behavior with the plastic limit unable to be meaningfully determined. Gradation analysis revealed 87.24% sand fraction and only 12.76% passing the No. 200 sieve, with a uniformity coefficient (Cu) of 6.67 and coefficient of curvature (Cc) of 0.60. Based on the USCS system, the soil is classified as SP (Poorly Graded Sand), while according to AASHTO it belongs to group A-3 (Non-plastic Fine Sand). The non-plastic nature of the soil indicates relative stability against moisture changes, making it suitable for use as fill material or road base layer, though susceptibility to erosion and liquefaction under saturated conditions should be considered. This research provides essential geotechnical baseline data for construction planning and further studies within the Politeknik Negeri Medan environment.